Viscoelastic axisymmetric structural analysis of flexible pipes in frequency domain considering temperature effect. (November 2016) - Liu, Junpeng; Vaz, Murilo Augusto
Abstract: Structural damping induced by material viscoelasticity in flexible risers may generate a non-ignorable effect on the global dynamic analyses. This paper presents an analytical model in frequency domain which is capable of predicting the structural viscoelastic behavior of flexible risers subjected to axisymmetric harmonic loads. In this model, the influence of temperature is taken into consideration, as well as the viscoelastic material properties, which are represented by Prony series. Shift factor as a function of temperature is observed through a series of experimental data. The material constants in Prony series are obtained through Levenberg-Marquardt curve-fitting method. This model yields an evident non-linear relationship between force and axial strain, posing a noticeable hysteresis loop. The loop circumscript area can be accurately calculated as the dissipated energy used for obtaining the axial structural damping. A case study is presented to illustrate the model application and it is found that the axial strains are inversely proportional to the frequency regardless of temperature. Furthermore, both axial strain and dissipated energy are seen to be dramatically affected by the interaction of frequency and temperature, but no strict law can be found. Highlights: Viscoelastic axisymmetric model in frequency is presented. At some frequencies and temperatures, the relationship between axial force and strain generates an obvious hysteresis loop. The effect of loading frequency on structural response is proposed. Influence of temperature is discussed. The agreement between frequency viscoelastic model and elastic model is excellent.